Dyrk1A phosphorylates alpha-synuclein and enhances intracellular inclusion formation - Kim, Eun Joo; Sung, Jee Young; Lee, Hyun Jung; Rhim, Hyewhon; Hasegawa, Masato; Iwatsubo, Takeshi; Min, Do Sik; Kim, Jongsun; Paik, Seung R.; Chung, Kwang Chul (AMER SOC BIOCHEMISTRY MOLECULAR BIOLOGY INC, 2006)
Lewy bodies (LBs) are pathological hallmarks of Parkinson disease (PD) but also occur in Alzheimer disease (AD) and dementia of LBs. alpha-Synuclein, the major component of LBs, is observed in the brain of Down syndrome (DS) patients with AD. Dyrk1A, a dual specificity tyrosine-regulated kinase (Dyrk) family member, is the mammalian ortholog of the Drosophila minibrain (Mnb) gene, essential for normal postembryonic neurogenesis. The Dyrk1A gene resides in the human chromosome 21q22.2 region, which is associated with DS anomalies, including mental retardation. In this study, we examined whether Dyrk1A interacts with alpha-synuclein and subsequently affects intracellular alpha-synuclein inclusion formation in immortalized hippocampal neuronal (H19-7) cells. Dyrk1A selectively binds to alpha-synuclein in transformed and primary neuronal cells. alpha-Synuclein overexpression, followed by basic fibroblast growth factor-induced neuronal differentiation, resulted in cell death. We observed that accompanying cell death was increased alpha-synuclein phosphorylation and intracytoplasmic aggregation. In addition, the transfection of kinase-inactive Dyrk1A or Dyrk1A small interfering RNA blocked alpha-synuclein phosphorylation and aggregate formation. In vitro kinaseassay of anti-Dyrk1A immunocomplexes demonstrated that Dyrk1A could phosphorylate alpha-synuclein at Ser-87. Furthermore, aggregates formed by phosphorylated alpha-synuclein have a distinct morphology and are more neurotoxic compared with aggregates composed of unmodified wild type alpha-synuclein. These findings suggest alpha-synuclein inclusion formation regulated by Dyrk1A, potentially affecting neuronal cell viability.
Keywords: HIPPOCAMPAL PROGENITOR CELLS; ELEMENT-BINDING PROTEIN; A-BETA COMPONENT; DOWN-SYNDROME; PARKINSONS-DISEASE; ALZHEIMER-DISEASE; LEWY BODIES; NEURONAL DIFFERENTIATION; PRECURSOR PROTEIN; SRC-FAMILY